2017
DOI: 10.1038/cdd.2017.53
|View full text |Cite
|
Sign up to set email alerts
|

DR5 and caspase-8 are dispensable in ER stress-induced apoptosis

Abstract: The endoplasmic reticulum (ER) stress response constitutes cellular reactions triggered by a wide variety of stimuli that disturb folding of proteins, often leading to apoptosis. ER stress-induced apoptotic cell death is thought to be an important contributor to many human pathological conditions. The molecular mechanism of this apoptosis process has been highly controversial with both the receptor and the mitochondrial pathways being implicated. Using knockout mouse models and RNAi-mediated gene silencing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 18 publications
5
49
1
Order By: Relevance
“…We also investigated PUMA expression, which is reported to be a proapoptotic gene induced by ERS [32]. Our results showed that melatonin suppressed PUMA expression stimulated by busulfan (P < 0.05, Fig.…”
Section: Resultssupporting
confidence: 51%
“…We also investigated PUMA expression, which is reported to be a proapoptotic gene induced by ERS [32]. Our results showed that melatonin suppressed PUMA expression stimulated by busulfan (P < 0.05, Fig.…”
Section: Resultssupporting
confidence: 51%
“…There are three main apoptosis pathways: the death receptor pathway, the mitochondrial pathway and the ER pathway . It has been confirmed that Mn can induce apoptosis via the involvement of ER stress and mitochondrial dysfunction .…”
Section: Discussionmentioning
confidence: 97%
“…There are three main apoptosis pathways: the death receptor pathway, the mitochondrial pathway and the ER pathway. 20 It has been confirmed that Mn can induce apoptosis via the involvement of ER stress and mitochondrial dysfunction. 7,21 The GRP78 protein is a key regulator in ER stress signalling pathways that are However, to cope with excessive ER stress, this protective signalling pathway was changed to a pro-apoptotic response.…”
Section: Discussionmentioning
confidence: 97%
“…6B). Moreover, PUMA, which has a pro-apoptotic role [34], was increased significantly, and Îł-H2AX, a DNA damage marker indicating cell apoptosis [30,33], also accumulated significantly (Fig. 6B).…”
Section: Ra190 Induces G 2 -M Phase Cell Cycle Arrest and Apoptosis Omentioning
confidence: 94%